2020
DOI: 10.3233/jad-190759
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and the Risk of Alzheimer’s Disease: The Rotterdam Study

Abstract: There is a wide interest in biomarkers that capture the burden of detrimental factors as these accumulate with the passage of time, i.e., increasing age. Telomere length has received considerable attention as such a marker, because it is easily quantified and it may aid in disentangling the etiology of dementia or serve as predictive marker. We determined the association of telomere length with risk of Alzheimer's disease and all-cause dementia in a population-based setting. Within the Rotterdam Study, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 35 publications
(39 reference statements)
7
47
1
Order By: Relevance
“…One potential explanation for this could be the enhanced level of oxidative stress in those patients (Levstek et al, 2020 ). In a more recent study, however, a U-shaped association between the TL and the risk for Alzheimer's disease was demonstrated, with both shorter and longer telomeres associated with an increased risk of this disease in the general population (Fani et al, 2020 ). Given the uncertainty of findings, the contribution of telomere attrition in the pathogenesis of neurodegenerative disorders is yet to be fully elucidated (Levstek et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…One potential explanation for this could be the enhanced level of oxidative stress in those patients (Levstek et al, 2020 ). In a more recent study, however, a U-shaped association between the TL and the risk for Alzheimer's disease was demonstrated, with both shorter and longer telomeres associated with an increased risk of this disease in the general population (Fani et al, 2020 ). Given the uncertainty of findings, the contribution of telomere attrition in the pathogenesis of neurodegenerative disorders is yet to be fully elucidated (Levstek et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…However, there was a more significant telomere shortening every year among individuals with AD than in healthy individuals and those with MCI. Although shorter TLs are associated with AD [ 20 ], several studies have reported that TL is not always shorter in patients with AD than in healthy individuals [ 13 15 ]. Thus, TL might not be the major determinant of AD because then one might expect that individuals would develop AD as soon as telomeres shorten to a certain size [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TL might not be the major determinant of AD because then one might expect that individuals would develop AD as soon as telomeres shorten to a certain size [ 14 ]. In addition, a recent study found that both shorter and longer TLs were associated with an increased risk of AD [ 15 ]. Our findings demonstrated more rapid telomere shortening per year in individuals with AD than in healthy individuals and those with MCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations